Test-retest reliability of four flatwater performance-related tests in canoe slalom athletes - Vajda, M.; Krupa, F.; Busta, J.; Pratt, J (Frontiers in Physiology, 2023)
Purpose: This study aims to evaluate the test-retest reliability of four flatwater performance-related tests in canoe slalom athletes.